Iceland : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2001)
Iceland has implemented a broad-based program of financial liberalization and market reforms. Iceland's conduct of monetary and financial policies is highly transparent, which contributes in an important way to the stability and efficiency of the financial system. Both macroprudential and microprudential indicators suggest that the system may be vulnerable to a macroeconomic shock. The Icelandic financial system is vulnerable to market risk and credit risk. The government intends to use the results of the assessment to strengthen their operations and enhance improvements to the regulatory framework.